Effect of Logistics Management Practices on Supply Chain Performance of Manufacturing Firms in Kenya - Muema, Mercy Mwende; Achuora, Dr. John (International Journal of Supply Chain and Logistics, 2020)
Purpose: The aim of this study was to analyze the impact of logistics management on success of supply chain among Kenyan manufacturing companies. Methodology: A descriptive research design was adopted. The objective populace of the investigation was all the 708 assembling firms in Kenya authorized under Kenya Association of Manufacturers the year 2017. An equation was utilized to choose 96 firms out of the complete 708 firms. The head of acquirement from each firm was focused as the unit of perception. Quantitative essential information was gathered by the examination. The investigation utilized both enlightening and inferential measurements for examination. A relapse model was utilized to set up the connection between the factors. SPSS adaptation 21 was utilized for information examination. Information discoveries was exhibited through tables and figures. Results and conclusion: The study found that warehousing management positively and significantly affects supply chain performance of manufacturing firms in Kenya. The results further showed that inventory management practices positively affect the supply chain performance of manufacturing firms. Consequently, order processing management was found to positively affects the supply chain performance of manufacturing firms in Kenya. The study finally established that transportation management positively affects the supply chain performance of manufacturing firms in Kenya. Unique contribution to theory, policy and practice: The study prescribes that the administration of assembling firms should consolidate the practices into their framework so as to improve their presentation and competitiveness. Strategic administrators of different assembling firms should lead every one of these pieces of training to guarantee that there is slicing of expenses through co-ordinations rehearses. The examination suggests for the upgrade stock control and the workforce needs outer direction concerning stock control. There is requirement for more opportunity to be taken in the procedures inside the distribution center. The association ought to have satisfactory stock control measures set up. The investigation additionally prescribes that it is important to designate stockroom assets proficiently and successfully to upgrade the efficiency and decrease the activity expenses of the distribution center. All assembling organizations and different associations ought to be encouraged to grasp the idea with the goal that they can probably receive the rewards of embracing these practices.